Three case studies in virtual preservation. Applying virtual reality to Cultural Heritage - Kai Reaver (Agathón)
The paper documents three case studies researching the techniques of Virtual Preservation upon various Cultural Heritage sites in order to preserve material aspects that, in the near future, can be irreparably damaged by the impact of climate change. Through the use of 3D scanners, photogrammetry, virtual and reality, and rendering software, the study documents how emerging technologies may be used together to digitally recreate full-scale Cultural Assets, for digital exhibition and archival. Although Virtual Preservation demands a substantial change of established working methods and tools, the paper argues that the realism obtained can compensate for the loss of the material of the Asset and still allow future generations to experience Cultural Heritage sites. The article concludes on illustrating the limitations and strengths of the study and foreseeing that Virtual Preservation can help experts to establish guidelines integrating virtual reality into traditional practice.